Water and food security in the Arabian gulf (The Emirates Center for Strategic Studies and Research, 2013)
In this book, water and food resource management strategies are examined, as well as the policies in the Gulf states, the global geopolitics of water security, future demand trends in the Gulf region, and the particular challenges faced by the UAE in ensuring a reliable supply of food and water in the coming decades.